(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2021)
The coronavirus crisis is an opportunity for Europe to bet on strategic interdependence and multilateralism. A more multilateral EU will only be possible if it emerges more united and solidary from this crisis with greater health coordination and a solid economic reconstruction plan focused on digitization and the environment, with a stronger euro at the international level and a full single market. Otherwise, current trends will lead to a Westphalian world in which Europe has little political clout.